Depression in Tuberculosis Patient: A literature Review - Aprilia, Indah (Scientia Psychiatrica, 2023)
Tuberculosis is one of the infectious diseases with the highest burden with the highest morbidity and mortality in the world. Tuberculosis is divided into two groups: latent tuberculosis and active tuberculosis. The diagnosis of tuberculosis can be established through anamnesis and investigations. Tuberculosis is often associated with levels of depression, the high incidence of depression in tuberculosis patients is caused by various factors including biological factors of the immune response system (IFN-g agents, TNF, IDO NALP3), social factors and behavioral factors. Management of anti-depressant therapy that is recommended as the first line is the SSRI group. Furthermore, patients with drug withdrawal or treatment failure, high risk of drug resistance, bad stigma about their disease will increase the risk of depression.